Modernization of the Feed Water Regenerative Heating System in the “PT-60” Steam Turbine Unit Cycle - V. V. Yanchuk; V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
At industrial CHP plants which are characterized, in particular, by steam supply to industrial consumers, in cases with significant condensate losses, it is proposed to develop a system of feed water regenerative heating by utilizing low-temperature waste heat flows those are available directly at the CHP plant. The regenerative use of low-temperature heat flows within the CHP that is proposed is possible only on the basis of heat pumps use. In this context, the use of electrically-driven heat pumps (EHP) and absorption heat pumps (AHP) is considered. It is shown that, despite the higher heating coefficient of the EHP, the thermodynamic (exergetic) efficiency and economic efficiency of the AHP are higher. Furthermore, the latter also has operational advantages. It is possible to use heat flows with various heat carriers as AHP drive, those are required for the transfer of thermal energy from a cold source to a hot receiver. In this paper, using the example of the “PT-60” steam turbogenerator unit, which is the most common type for CHP plants of the Belarusian power system, the indicators of the primary fuel use efficiency growth at the CHP plant for the AHP with a steam drive are determined. Three scenarios of the use of AHP as part of the thermal scheme of the CHP are considered, viz. with an increase in generation, with the maintenance of generation or with a decrease in the generation of electric energy. The latter is relevant in the current situation with the Unified Energy System of Belarus. In this case, while maintaining the minimum steam flow into the condenser of 12 t/h, the following increase in the plant efficiency has been obtained: electrical efficiency increased by 0.90 %, energy efficiency – by 0.55 %, and exergetic efficiency – by 0.23 %.